If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 = 6 + 5w Solving -29 = 6 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. -29 + -5w = 6 + 5w + -5w Combine like terms: 5w + -5w = 0 -29 + -5w = 6 + 0 -29 + -5w = 6 Add '29' to each side of the equation. -29 + 29 + -5w = 6 + 29 Combine like terms: -29 + 29 = 0 0 + -5w = 6 + 29 -5w = 6 + 29 Combine like terms: 6 + 29 = 35 -5w = 35 Divide each side by '-5'. w = -7 Simplifying w = -7
| 25-(x-7)=9x-2 | | 0=x^2-13x+42.25 | | (25/64)^-1/2 | | 6x-12=-9x | | 49=6b+9+2b | | (4x+8)(x+4)=480 | | v-17v=-6 | | 2x+2x=15 | | 3/7=z/63 | | 32.5p=260.0 | | 17/26=w/52 | | (-6x+-2)=-32-x | | 0-(-43)= | | e^3x-1=10 | | 3k+4k=12 | | 2x+3+4=7x+2x-14 | | 39/54=d/18 | | [b/5]=1 | | 32=4-4w | | 4x+6+3x=41 | | -8+x+5-7=20x-10 | | 27.50x+17=23.25x+17 | | 5(4x-3)+8=2 | | 6x+3=-2+11 | | (X-8y+2)*(3x-2c+100)=0 | | -25+(-16)= | | 2(7x+1)=86 | | 76(8686868686868686868686886866888+8)=7 | | 25/60=c/12 | | 7(-2x-3)=-7 | | x(16-x^2)^1/2 | | -10+v-17v=4 |